Pengaruh Efisiensi Anggaran terhadap Penyerapan Anggaran pada Dinas Pekerjaan Umum dan Penataan Ruang Kota Palembang - Bunga Suci Rahmadani; Fitriasuri Fitriasuri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effect of budget efficiency on budget absorption at the Public Works and Spatial Planning Agency of Palembang City. The background is the suboptimal level of budget absorption at the Public Works and Spatial Planning Agency of Palembang City, which is indicated by budget realization that has not reached 100% in recent years. This condition indicates the existence of factors that influence budget absorption, one of which is budget efficiency. This study uses a quantitative descriptive approach with primary data obtained through distributing questionnaires to 25 respondents related to the planning and finance division. Data analysis techniques are carried out through validity tests, reliability tests, classical assumption tests, simple linear regression, t-tests, and coefficients of determination. The results of the study indicate that budget efficiency has a positive and significant effect on budget absorption. The regression equation obtained is Y = 5.683 + 0.818X, with a calculated t value of 6.984 greater than the t table of 2.073 and a significance value of 0.000. The R-square value of 0.680 indicates that budget efficiency explains 68.0% of budget absorption, while the remaining 32.0% is influenced by factors outside this study. This finding suggests that increasingly efficient budget management can support more optimal budget realization in the public sector.